Chinese and UK participants' preferences for physical attractiveness and social status in potential mates - Zhang, Lingshan (R Soc Open Sci, 2019)
Men are hypothesized to show stronger preferences for physical attractiveness in potential mates than women are, particularly when assessing the attractiveness of potential mates for short-term relationships. By contrast, women are thought to show stronger preferences for social status in potential mates than men are, particularly when assessing the attractiveness of potential mates for long-term relationships. These mate-preference sex differences are often claimed to be ‘universal' (i.e. stable across cultures). Consequently, we used an established ‘budget-allocation' task to investigate Chinese and UK participants' preferences for physical attractiveness and social status in potential mates. Confirmatory analyses replicated these sex differences in both samples, consistent with the suggestion that they occur in diverse cultures. However, confirmatory analyses also showed that Chinese women had stronger preferences for social status than UK women did, suggesting cultural differences in the magnitude of mate-preference sex differences can also occur.